Study protocol of short-course radiotherapy combined with CAPOX and PD-1 inhibitor for locally advanced colon cancer: a randomised, prospective, multicentre, phase II trial (TORCH-C) - Yan Wang; Hui Zhang; Fangqi Liu; Sanjun Cai; Lijun Shen; Zhen Zhang; Yaqi Li; Ruiyan Wu; Fan Xia; Shujuan Zhou; Yaqi Wang; Yajie Chen; et al. (BMJ Open, 2024)
Introduction The preliminary result of the TORCH trial has shown a promising complete response (CR) for managing locally advanced rectal cancer with neoadjuvant short-course radiotherapy (SCRT) combined with chemotherapy and PD-1 inhibitor. For locally advanced colon cancer (LACC) with bulky nodal disease and/or clinically T4, neoadjuvant chemotherapy followed by colectomy with en bloc removal of regional lymph nodes is the suggested treatment. However, the CR rate is less than 5%. TORCH-C will aim to investigate neoadjuvant SCRT combined with chemotherapy and PD-1 inhibitor in LACC.Methods and analysis TORCH-C is a randomised, prospective, multicentre, double-arm, open, phase II trial of SCRT combined with chemotherapy and immunotherapy in LACC with microsatellite stable (MSS) patients and cT4 or bulky nodes. Eligible patients will be identified by the multidisciplinary team. 120 patients will be randomised 1:1 to the intervention or control arm. The patients in the control arm will receive four cycles of capecitabine plus oxaliplatin (CAPOX). The patients in the intervention arm will receive SCRT, followed by four cycles of CAPOX and PD-1 inhibitor (serplulimab). Both arms will receive curative surgery, followed by four cycles of CAPOX. The primary endpoint is pathological complete regression.TORCH-C (TORCH-colon) trial aims to investigate whether the combination of immunotherapy and chemoradiotherapy improves the treatment effect in LACC with MSS. TORCH-C will establish the TORCH platform, a key part of our long-term strategy to develop neoadjuvant treatment for colorectal cancer.Ethics and dissemination This study was approved by the Ethics Committee of Fudan University Shanghai Cancer Center (approval number: 2211265-12).Trial registration number NCT05732493